VCKSM: Verifiable conjunctive keyword search over mobile e-health cloud in shared multi-owner settings - MIAO, Yinbin (Institutional Knowledge at Singapore Management University, 2017)
Searchable encryption (SE) is a promising technique which enables cloud users to conduct search over encrypted cloud data in a privacy-preserving way, especially for the electronic health record (EHR) system that contains plenty of medical history, diagnosis, radiology images, etc. In this paper, we focus on a more practical scenario, also named as the shared multi-owner settings, where each e-health record is co-owned by a fixed number of parties. Although the existing SE schemes under the unshared multi-owner settings can be adapted to this shared scenario, these schemes have to build multiple indexes,which definitely incur higher computational overhead. To save bandwidth and computing resources in cloud servers and guarantee the correctness of search results, we present a secure cryptographic primitive, namely verifiable conjunctive keyword search over mobile e-health cloud scheme, in the shared multi-owner settings by utilizing multi signatures technique. Formal security analysis proves that our scheme is secure against the keyword guessing attacks in standard model. Empirical study using a real-world dataset justifies that our scheme is efficient and feasible in practical applications.